The effect of servant leadership on hotel employees' behavioral consequences: Work engagement versus job satisfaction - Ozturk, Anastasia; Karatepe, Osman M.; Okumus, Fevzi (Elsevier Sci Ltd, 2021)
Our paper explores the impact of servant leadership on absenteeism, in-role performance, and extra-role performance via the mediating roles of work engagement and job satisfaction. Our study utilized hotel employeesupervisor dyadic data with time-lagged measurement collected in Russia. Study results reveal that the positive effect of servant leadership on work engagement is stronger than on job satisfaction. As hypothesized, work engagement is a mediator between servant leadership and job satisfaction. The mediation influence of work engagement in the linkage between servant leadership and absenteeism is greater than the mediation influence of job satisfaction. This is also true for the mediation impact of work engagement in the association between servant leadership and in-role and extra-role performances. These findings enhance current understanding about the effectiveness of work engagement versus job satisfaction regarding the effect of servant leadership on behavioral consequences.
Keywords: Absenteeism; Hotel employees; Job performance; Job satisfaction; Russia; Servant leadership; Work engagement